Material capturado e utilizado na alimentação de Polybia (Trichothorax) Sericea (Olivier, 1791) (Hymenoptera, Vespidae) - Machado, Vera Lígia Letízio [UNESP]; Gobbi, Nivar [UNESP]; Alves Junior, Valter Vieira [UNESP] (Sociedade Brasileira de Zoologia, 1988)
The prey items utilized by Polybia (Trichothorax) sericea comprise 6 orders of Insecta (Lepidoptera, Hymenoptera, Collembola, Hemiptera and Odonata) and 1 order of Arachnida (Araneae), with a preference for larvae of Lepidoptera. The average protein weight transported was 15.3 mg, and the estimated daily weight was 522.6 mg, which indicates more than 12,000 prey a year.

As presas utilizadas por Polybia (Trichothorax) sericea compreendem 6 ordens de insetos (Lepidoptera, Hymenoptera, Collembola, Hemiptera e Odonata) e 1 ordem de Arachnida (Araneae), com preferência por larvas de Lepidoptera. A média de proteína transportada é de 15,3 mg e o peso diário estimado é de 522,6 mg, o que indica mais de 12000 presas por ano.